(3GdEJLGgGJ GdMOjKI aj OQGSGJ h HMhK YdGbI GdLeghQ HGdEfJQfJ h GdEYdGe GdLOjO (B/s - (3Sdje, MfGf CMeOs ((3eUQ (B:s (3LGeYI CSjhW cdjI GdCOGH bSe GdEYdGe ,s, 2013)
(3gOaJ GdOQGSI Gdi GdJYQa Ydi GHQR GdGJLGgGJ GdYdejI GdMOjKI aj OQGSGJ h HMhK YdGbI GdLeghQ HGdGfJQfJ h GdGYdGe GdLOjO ef MjK eLGdGJ GdGgJeGe GdHMKj h GdLhGfH GdefgLjI GdeSJNOeI h Pdc ef NdGd eSM GdGfJGL GdYdej aj GdOhd GdYQHjI h GdGLfHjIs
(3HHdjhZQGajG (B: (3U(B.118-131s
Keywords: (3GdEfJQfJ s; (3GdLeghQs; (3GdEYdGe GdLOjOs; (3dEJLGgGJ GdMOjKI s